The Effects of Market Access and Logistics Efficiency on The Competitiveness of Salt Farmers in Jeneponto Regency - Nurul Fadilah Aswar; Hasmyati; Nur Indah Atifah Anwar; Dian Anggraece Sigit Parawansa; Muhammad Ichwan Musa (Economics and Business Journal (ECBIS), 2026)
constrained by limited buyer options, price-information gaps, high distribution costs, inadequate storage facilities, and fragmented product flows. This study examines the effects of market access and logistics efficiency on the competitiveness of salt farmers. A quantitative explanatory survey was conducted with 100 active salt farmers. The three constructs were measured using a five-point Likert-scale questionnaire and analyzed through multiple linear regression. Market access had a positive and statistically significant effect on competitiveness (p < 0.05), indicating that broader buyer networks, timely price information, alternative marketing channels, and stronger negotiating opportunities improve farmers’ ability to reach markets and sustain sales. Logistics efficiency also had a positive and significant effect (p < 0.05); reliable transportation, lower distribution costs, appropriate storage, proper handling, and shorter delivery times help preserve quality and reduce avoidable losses. The simultaneous test confirmed that both variables jointly affected competitiveness (p < 0.05). These findings indicate that increasing production alone is insufficient when farmers cannot reach profitable markets through efficient product flows. Collective marketing, transparent market information, shared storage, coordinated transportation, and direct relationships with processing industries are therefore essential for strengthening farmers’ bargaining power and market performance